Real Money Balances in the Production Function of a Developing Economy: A Preliminary Study of the Malaysian Agricultural Sector - Habibullah, Muzafar Shah (1988)
Recent empirical evidence suggest that real money balances can be treated as a productive input in production. The reason for incorporating real money balances as a factor of production is because real money balances as a medium of exchange facilitate adjustments between capital and labour for specialization purposes and thus increase productivity. This study is an attempt to empirically test the evidence that real money balances is an input in the production function of the Malaysian agricultural sector. The results suggest that real money balances play significant role as a productive input in the production function of the Malaysian agricultural sector.